Low cost removal of reactive orange 16 dye using cross-linked chitosan/oil palm ash composite beads - Masitah, Hassan; H., H. Bassim; A., A. Latif; Zulfakar, Mokhtar; Naimah, Ibrahim; Salwa, Mohd Zaini Mokhtar (Universiti Malaysia Sabah (UMS), 2011)
3rd International Conference on Chemical and Bioprocess Engineering 2009 (ICCBPE-2009) / 23rd Symposium of Malaysian Chemical Engineers 2009 (SOMChE-2009) organized by Universiti Malaysia Sabah from 12th - 14th August 2009 at Sutera Harbour Golf Resort, Kota Kinabalu, Sabah, Malaysia.